E-construction: in relation of implementation in local authorities / Romuald Kuha Pius Kuha - Pius Kuha, Romuald Kuha (2003)
Construction is the most important industry that contributes towards the development of our nation. Physically all the effort should be provided in order to cater for the best quality of buildings being constructed. Construction plays a big role as the measurement of the growth and modernisation of the nation. However, construction doesn’t only involve on the matter of bricks and concretes. There are aspects in the construction we have not overview in details. The laymen would say construction is a rough industry when people standing in the middle of the construction field doing their job. As the world approach to the era of globalisation, every things changes and evolving in order to “survive”. And as time passes, constructions industry is still left behind due to the mindset as mentioned above. Bring the computer technology is the approach towards creating and enhancing the industry to a new platform. The question will arise to what extend will the industry uses the technology? Thinking of what to come and to expect of the industry in the near future, the most intruding word is e-construction. Over the years, all sort of “e” or electronic phases had been spreading around to introduce the new technology of electronic based application. We are quite familiar with the phases e-banking as it is practised in the financial businesses. How about e-construction? Being in one of “the citizen” in the constructions industry’s community, the idea of understanding more and gain view of knowledge about e-constructions was the first initiatives in developing the research. Along the way, the author try to focus on the area which e-construction have strong base of development, the author directed the study to the main player of the industry- Local Authorities. Regardless to the still new and young on information upon the topic, the dissertation intended to reveal the current scenarios of e-construction implementation in the local authorities. Giving information based on the author direction in seeing findings on the effectiveness of ICT application, the research came up with the result of ICT application on their daily tasks in Local Authority and view the planning and steps taking towards the vision of computerisation era.